Schools development and locations: the impact of distributions and parents perception of school performances - Mohamed Osman, Mariana; Bachok, Syahriah (s.n, 2012)
Study on school development and location includes the traffic safety of children in school as well as parent criteria in selecting school. School location played an essential role in school planning and development. beside became the criteria for parents in selecting school, it also determined the mode choice on the journey to school with built environmental. Parent taking children to school by private vehicle contributes to the impact on traffic flow during peak hour on weekdays. Parent dropping of and picking up their children to and from school increase vehicle queuing around the school area that create further congestion in and around the school area. The research also deals with the elements and problem that always being taken into consideration by the parents when choosing school for their children